A decade of shaping the futures of polar early career researchers: A legacy of the International Polar Year. (14th February 2019) - Hindshaw, Ruth S.; Mariash, Heather; Vick-Majors, Trista J.; Thornton, Alexander E.; Pope, Allen; Zaika, Yulia; Lenz, Josefine; Nielsen, Hanne; Fugmann, Gerlis
Abstract: The Association of Polar Early Career Scientists (APECS) is an important legacy of the International Polar Year (IPY). APECS continues to foster engagement in education, outreach and communication (EOC) activities relating to the polar regions and provide training for early career researchers (ECRs). We highlight opportunities for training, leadership and skills development, such as the annual Polar Weeks and Antarctica Day celebrations. Participation and engagement in EOC activities actively contributes to career development by enabling ECRs to develop valuable soft skills such as networking, communication and interdisciplinary knowledge. A pilot survey on EOC engagement highlighted that those who organise events also gain leadership skills such as team management. We discuss several factors contributing to the success of APECS in training the next generation of polar leaders. These include the geographical rather than discipline-specific focus of the organisation, utilisation of online resources, including social media, and the strong links with partner organisations. These examples demonstrate how the EOC legacy of IPY has continued due to APECS' targeted efforts to create EOC opportunities and provide skills and leadership training for ECRs.